2020
DOI: 10.1038/s41598-020-68741-5
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine and genome-wide DNA methylation investigation in behavioral addiction

Abstract: Won 2 , tomonari Morita 2 , emi ishikawa 2 , Young-A Lee 3 & Yukiori Goto 1* Behavioral addiction (BA) is characterized by repeated, impulsive and compulsive seeking of specific behaviors, even with consequent negative outcomes. in drug addiction, alterations in biological mechanisms, such as monoamines and epigenetic processes, have been suggested, whereas whether such mechanisms are also altered in BA remains unknown. in this preliminary study with a small sample size, we investigated monoamine concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Comparisons between KM and PP patients with a larger sample size will be required for the future study to further characterize whether there is difference of negative affects, depending on symptom types. Notably, we have recently shown using the genome-wide methylation analysis that DNA methylation status is different between KM and PP patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between KM and PP patients with a larger sample size will be required for the future study to further characterize whether there is difference of negative affects, depending on symptom types. Notably, we have recently shown using the genome-wide methylation analysis that DNA methylation status is different between KM and PP patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the experiences of craving and elation related to engaging in problematic behavior among patients with KM are consistent with those of addiction. We have previously shown that some affective and physiological features observed in KM patients overlap with those reported in individuals with drug addiction ( Asaoka et al, 2020a , 2020b , 2020c , 2021 ). However, insufficient studies still make it difficult to comprehensively understand KM as a behavioral addiction, and further investigation is required.…”
Section: Introductionmentioning
confidence: 74%
“…The genome-wide DNA methylation assays have shown the alterations in DNA methylation status in blood of drug addiction patients (Cecil et al, 2016). It has been reported that DNA methylation level is altered in METH addicted patients (Liu et al, 2020) and in the children of METH addicted parent (Asaoka et al, 2020). There was hypermethylated or hypomethylated CpG in brain tissues of drug addiction patients.…”
Section: Methylation and Methamphetamine Addictionmentioning
confidence: 96%
“…There was hypermethylated or hypomethylated CpG in brain tissues of drug addiction patients. In addition, some gene methylation was found in the candidate genes involved in drug addiction and other psychiatric disorders (Papageorgiou et al, 2019;Asaoka et al, 2020). BDNF methylation was increased in the PFC of METH-addicted rats and patients, but was decreased in the Hip of rats (Iamjan et al, 2021).…”
Section: Methylation and Methamphetamine Addictionmentioning
confidence: 99%